2016
DOI: 10.1007/s10930-016-9666-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of IGF-1R Gene and Polymorphisms of its Regulatory Regions in Different Pig Breeds

Abstract: Insulin like growth factor 1 receptor (IGF-1R) is a candidate gene for growth and carcass traits in regulating animal growth, metabolism and endocrine. It is widely expressed in liver, muscle, bone tissues where the IGF-1R functions as a factor that promotes cell growth. In this study, the protein expression level of IGF-1R gene in liver and muscle tissues of three periods (birth, weaning and adult) of three pig breeds (BamaXiang pigs (BM), Tibetan pigs (TM) and Junmu No.1 pigs (JM)) were tested by western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…That is to say, the gene may change its transcriptional level through alternative splicing, thereby affecting its function. In our previous studies, IGF-1R protein in Landrace pig was significantly higher than that in BaMa pig at birth (Cheng et al, 2016). However, in this study, the mRNA expression level of IGF-1R in Landrace and BaMa pigs showed no significantly different.…”
Section: Expression Of Igf-1r Iso01 and Igf-1r As02 In Different Pig contrasting
confidence: 81%
See 1 more Smart Citation
“…That is to say, the gene may change its transcriptional level through alternative splicing, thereby affecting its function. In our previous studies, IGF-1R protein in Landrace pig was significantly higher than that in BaMa pig at birth (Cheng et al, 2016). However, in this study, the mRNA expression level of IGF-1R in Landrace and BaMa pigs showed no significantly different.…”
Section: Expression Of Igf-1r Iso01 and Igf-1r As02 In Different Pig contrasting
confidence: 81%
“…In this study, BaMa pigs were chosen as the representative model of the miniature pigs and Landrace pigs (adult mean body weight, 250 kg) as large pig breeds. The two pig breeds were opposite in many growth characters but they were all genetically stable and their genetic backgrounds were clear (Cheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the Bama Xiang pig is a well-known miniature pig breed from Guangxi Zhuang Autonomous Region. It is characterized by highly inbred, stable heredity and mini-body size (the mean body weight of adults is nearly 40 kg) (Cheng et al, 2016;Yang et al, 2018). The Large White pig also called Yorkshire pigs, is considered the most representative of large pigs because of its large body size and high growth rate (mean body weight of adults is almost 250 kg) and is considered as the most typical representative of large pigs.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1R exhibits different protein expression levels in the liver and muscle tissues of large and miniature pigs (Cheng et al, 2016). A previous study screened nine strong linkage synonymous mutations in the coding sequence (CDS) of IGF-1R between large and miniature pigs, four of which were found in the extracellular domain (ECD), whereas five were located in the intracellular domain (ICD) (Changhong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor-1 receptor (IGF-1R) is found on the surface of many kinds of cells, including hepatocytes, myocytes, and osteocytes (Cheng et al, 2016). Recent studies suggest that IGF-1R is involved in both glucose and bone metabolism (Pelosi et al, 2017;Solomon-Zemler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%